Numerical investigation of T-shaped soil-cement column supported embankment over soft ground - Yi, Yaolin (2020)
Deep mixing is a technique to stabilize soft soils in situ by mixing with cementitious binders to form columns. An innovative soil-cement column is proposed, with an enlarged column cap at shallow depth, and as such the column shape is analogous to a letter “T”. This paper presents a numerical investigation on the performance of T-shaped soil-cement column supported embankment over soft ground. The sensitivity of differential settlement between soil and column, as well as soil and column stresses in the middle of the embankment to the diameter and the height of the enlarged column cap is systemically studied.